Use of Polymethyl Methacrylate-Based Cement for Cosmetic Correction of Donor-Site Defect following Transposition of Temporalis Myofascial Flap and Evaluation of Results after Adjuvant Radiotherapy - Mandlik, Dushyant; Gupta, Karan; Patel, Daxesh; Patel, Purvi; Toprani, Rajendra; Patel, Kaustubh (Journal of Reconstructive Microsurgery, 2015)
Background Temporalis myofascial flap is a versatile flap for reconstruction of the oral cavity defects, but results in an esthetically compromised deformity at the donor site. We used polymethyl methacrylate (PMMA) cement to correct the volume loss defect caused by temporalis myofascial flap and evaluated its results before and after adjuvant radiotherapy.Methods We discuss our experience of using PMMA cement to augment donor-site deformity in 25 patients (17 males, 8 females) between years 2005 and 2009. The primary defect was a result of the ablative surgery for squamous cell carcinoma of the upper alveolar and the buccoalveolar sulcus. A modified curved hemicoronal incision was used as an access for better cosmetic outcome. The volume of cement required was decided during the surgery.Results All patients are in regular follow-up, alive and free of complications at implant site, except one patient who developed wound dehiscence. The condition of the implant was evaluated by postoperative computed tomographic scan, repeated after adjuvant radiotherapy in cases required. There were no radiation-induced changes in the contour and volume of the implants. Cosmetic result of the implant was reported satisfactory by the patients postoperatively.Conclusion Restoration of the temporal area defect after the temporalis myofascial flap harvest with the use of PMMA cement is an easy and safe method, with excellent esthetic results. The implant is stable and resistant to any changes in contour and loss of volume even after adjuvant radiotherapy, with no added morbidity to the patients.
Keywords: maxillectomy; temporalis myofascial flap; polymethyl methacrylate cement; temporoplasty